1999
DOI: 10.1161/01.res.85.10.959
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial ST Depression in Acute Myocardial Infarction

Abstract: Abstract-The presence of electrocardiographic ST depression in acute infarction remains controversial and poorly explained. A combined animal and modeling study was performed to evaluate the source of ST changes in acute infarction. In anaesthetized sheep, small infarcts showed uniform ST elevation over the infarction whereas larger infarcts showed marked ST depression over the normal myocardium in addition to the ST elevation. These findings were replicated by bidomain models of the heart. A hollow sphere was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…The model also predicts ST depression just outside the ischaemic boundary and this depression increases in magnitude as the size of the ischaemic region increases. This fact was also observed by Li et al [23]. Model predictions also fit with the simple model of Holland and Brooks [11].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The model also predicts ST depression just outside the ischaemic boundary and this depression increases in magnitude as the size of the ischaemic region increases. This fact was also observed by Li et al [23]. Model predictions also fit with the simple model of Holland and Brooks [11].…”
Section: Discussionsupporting
confidence: 84%
“…2-4). In each case, the highest amplitude of ST elevation was obtained at the boundary of the ischaemic region, as was observed by Li et al [23] with ligation of the LAD and LCX arteries. However, this behavior was not observed with the occlusion of the obtuse marginal artery, nor was it observed in the experimental studies of Smith et al [12] where a more convex distribution was observed.…”
Section: Discussionsupporting
confidence: 74%
“…One way to locate ischemia in clinical electrocardiography is the so-called ST segment elevation in the electrocardiogram (ECG), but both the choice of this criterion and the mechanism underlying ST shifts are still controversial. Several experimental works have studied these phenomena: Samson et al [453], Prinzmetal et al [403], Kjekshus et al [286], and Kleber et al [279], suggested that subendocardial ischemia produces ST elevation at the epicardial level, while Wolferth et al [565] and Li et al [298] found ST depression. MacLeod et al [314] observed depression only under conditions of combined coronary occlusion and elevated heart rate.…”
Section: Subendocardial Ischemia St Depression and Elevationmentioning
confidence: 99%
“…Many important results can be obtained with ''static'' simulations of ischemia, in which only the effect of the offset in resting V m is simulated [19,23,24,29,31,34]. For such simulations, the profile of resting V m across the ischemic border is of interest.…”
Section: Cellular Couplingmentioning
confidence: 99%